United by their rights: Feminists and teachers in 1924 - Solano Arias, Marta (2012)
A retrospective about some of the battles for women's rights, allows us to reconsider the strategies for the present, leaving a great lesson on the importance of articulating efforts and the creation of alliances which cross the traditional boundaries of women's differences. Created to obtain the vote for women, Liga Feminista Costarricense (Costa Rican Feminist League) is able to channel and face upto other challenges unresolved still today, such as sexual exploitation of girls and women, or the fight for equal pay for equal jobs.